1984
DOI: 10.1037/0096-3445.113.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and skill in typing.

Abstract: What are the factors responsible for skilled typing performance, and do they change with the age of the typist? These questions were addressed in two studies by examining time and accuracy of keystrokes in a variety of typinglike activities among typists ranging in speed from 17 to 104 net words per minute and ranging in age from 19 to 72 years old. Typing skill was related to the temporal consistency of making the same keystroke, the efficiency of overlapping successive keystrokes, the speed of alternate-hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

39
378
8
9

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 496 publications
(434 citation statements)
references
References 57 publications
39
378
8
9
Order By: Relevance
“…For instance, Charness's (1981) study of chess players found that high levels of performance could be maintained as performers got older. Other examinations of cognitive-motor experts such as pianists (Krampe & Ericsson, 1996) and typists (Salthouse, 1984) substantiate these findings. These investigations point to the critical role that prolonged involvement (i.e., training) might play in maintaining performance.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…For instance, Charness's (1981) study of chess players found that high levels of performance could be maintained as performers got older. Other examinations of cognitive-motor experts such as pianists (Krampe & Ericsson, 1996) and typists (Salthouse, 1984) substantiate these findings. These investigations point to the critical role that prolonged involvement (i.e., training) might play in maintaining performance.…”
mentioning
confidence: 75%
“…The costs associated with longitudinal research, however, often preclude the systematic examination of age-related decline. Several researchers (Bortz & Bortz, 1996;Stones & Kozma, 1981, 1984 have suggested that masters athletes represent an ideal population for examining age-related decline because the comprehensive record keeping associated with many sports affords readily accessible measures of performance over time. Furthermore, data from masters athletes can be used to represent the performance levels possible if one maintains involvement in high amounts of physical activity throughout the life span.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typewriting involves controlling complex sequences of keystrokes while concentrating on copying or composing complex sentences. Yet, skilled typists type very quickly compared with novices (Butsch, 1932;Fendrick, 1937;Salthouse, 1984). The differences between skilled typists and novices stem from the way typing is controlled (Bryan & Harter, 1899;Lashley, 1951;Logan & Crump, 2011).…”
Section: Hierarchical Control Of Skilled Performancementioning
confidence: 99%
“…Research by Salthouse (1984) on typing skills in old age is one persuasive example of how specialization and compensation interact in older adults to produce a high level of selective efficacy. Older expert typists-although showing less efficient reaction times than young expert typists when confronted with the typing of individual characters-nevertheless display good efficacy.…”
Section: Intellectual Development As a Dynamic Between Growth (Gain) mentioning
confidence: 99%